El santoral hispano-mozárabe: Fuentes para su estudio - Ramis Miquel, Gabriel (Verbum vitae, 2025)
The study of the cycle of saints in liturgical books sheds light on the evolution of the cult of the saints in a given rite or Church. Through such a study, we can trace the theological and historical evolution of the calendar of saints. This article aims to systematically present the sources of the liturgy of the Spanish-Mozarabic rite, which will be useful for later research on the calendar of saints. It is divided into two parts: manuscripts and printed sources. This covers the entire timeline of liturgical books and presents all sources of the A and B traditions of the Office and the Mass, including the liturgical calendars. The manuscripts date from the late 7th or early 8th century to the 12th century, and the printed sources date from 1500 to the present day. The lack of records from the early years of Christianity makes studying the cycle of saints difficult. Of course, the Churches of the Iberian Peninsula celebrated the feasts of the saints before the eighth century, but no liturgical records survived. Most sources date from the 10th to 12th centuries, a time when the Spanish liturgy’s calendar of saints took shape and the number of feast days of saints venerated by other Churches significantly increased. With the publishing of the Missal and the Breviary by Cardinal Cisneros, the feast days of saints originating from Roman sources were added to the calendar.